Cytidine Diphosphate-Ribitol Analysis for Diagnostics and Treatment Monitoring of Cytidine Diphosphate-l-Ribitol Pyrophosphorylase A Muscular Dystrophy. (1st October 2019) - van Tol, Walinka; van Scherpenzeel, Monique; Alsady, Mohammad; Riemersma, Moniek; Hermans, Esther; Kragt, Else; Tasca, Giorgio; Kamsteeg, Erik-Jan; Pennings, Maartje; van Beusekom, Ellen; Vermeulen, Jeroen R; van Bokhoven, Hans; et al.
Abstract: BACKGROUND: Many muscular dystrophies currently remain untreatable. Recently, dietary ribitol has been suggested as a treatment for cytidine diphosphate (CDP)-l -ribitol pyrophosphorylase A (CRPPA, ISPD), fukutin (FKTN), and fukutin-related protein (FKRP) myopathy, by raising CDP-ribitol concentrations. Thus, to facilitate fast diagnosis, treatment development, and treatment monitoring, sensitive detection of CDP-ribitol is required. METHODS: An LC-MS method was optimized for CDP-ribitol in human and mice cells and tissues. RESULTS: CDP-ribitol, the product of CRPPA, was detected in all major human and mouse tissues. Moreover, CDP-ribitol concentrations were reduced in fibroblasts and skeletal muscle biopsies from patients with CRPPA myopathy, showing that CDP-ribitol could serve as a diagnostic marker to identify patients with CRPPA with severe Walker–Warburg syndrome and mild limb-girdle muscular dystrophy (LGMD) phenotypes. A screen for potentially therapeutic monosaccharides revealed that ribose, in addition to ribitol, restored CDP-ribitol concentrations and the associated O-glycosylation defect of α-dystroglycan. As the effect occurred in a mutation-dependent manner, we established a CDP-ribitol blood test to facilitate diagnosis and predict individualized treatment response. Ex vivo incubation of blood cells with ribose or ribitol restored CDP-ribitol concentrations in a patient with CRPPA LGMD. CONCLUSIONS: Sensitive detection of CDP-ribitol with LC-MS allows fast diagnosis of patients with severe and mild CRPPA myopathy. Ribose offers a readily testable dietary therapy for CRPPA myopathy, with possible applicability for patients with FKRP and FKTN myopathy. Evaluation of CDP-ribitol in blood is a promising tool for the evaluation and monitoring of dietary therapies for CRPPA myopathy in a patient-specific manner.